The Influence of E-Learning Systems on Student Learning Outcomes in Event Organizer Course - Yuzia Eka Putri (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2021)
This research is motivated by the low value of students in the event organizer subjects observed since online learning. This study aims to look at the influence of online learning system variables on the learning outcomes of Unimed culinary students. This research was classified as quantitative research. The research population was students in the culinary Studies program, while the sample was food students who completed the event organizer course. The data analysis technique used was descriptive data analysis. The data analysis requirements test consisted of normality and homogeneity tests, and hypothesis testing with the